Exploration into practical significance of integral water permeability of textile vascular grafts. (July 2021) - Guan, Guoping; Yu, Chenglong; Fang, Xuan; Guidoin, Robert; King, Martin W; Wang, Hongjun; Wang, Lu
Water permeability of textile vascular grafts has been considered as a key indicator for predicting blood permeability after implantation. However, a correlation between water and blood permeability has not been established yet. Therefore, even though the water permeability of a vascular graft can be tested according to the standard ISO 7198, the results fail to guide a manufacturer or a surgeon to judge whether this vascular graft needs pre-clotting or not prior to implantation. As a result, all commercial graft products show almost zero water permeability, which leads to the loss of advantages that textile vascular grafts have the pore size-controlled porous wall. To solve this problem, four types of woven vascular grafts were designed and manufactured in the present work. Then their permeability to water, simulated plasma, and anticoagulated whole blood were measured at graded pressures from 8 to 16 kPa. Moreover, the correlations among the water permeability, the simulated plasma permeability, and the anticoagulated whole blood permeability were established. The results suggest that relatively steady correlations exist between the water permeability and the anticoagulated whole blood permeability, and that the evaluation of the blood permeability using the water permeability is feasible and objective. The present work provides a quantitative method for evaluating the blood permeability using the water permeability, and the latter is thus endowed with practical significance for guiding designs and clinical pre-clotting operations of textiles vascular grafts.